PENGARUH LINGKUNGAN PEKERJAAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi Pada Bank Jateng Cabang Utama Semarang ) - Erika Putri Pratiwi, 11.5202.0041 (Students Journal of Economic and Management, 2013)
The purpose of this research to analysis  the influences work environment and job characteristics to employee performance with organizational commitment as mediating variable. The research used multiple regression analysis method, to analyze the influences of independent variable (work environment and job characteristics) to dependent variable (organizational commitment, and employee performance)  The sample  in this research are employee at Bank Jateng Cabang Utama Seamarang. To obtain the sample use purposive sampling with two  crriteria, from this criteria are obtain the sample of 107 employee. Based on the results of data analysis this research concludes some of the following  (1)Work environment and job characteristics  influence organizational commitment (2) Work environment, job characteristics,  organiztional commitment influence employee. Performance (3)Organizational commitment can not mediate the influence of work environment to employee performance .(4) Organizational commitment can not mediate the influence of job characteristics to employee performance. Key words : work environment, job characteristics, organizational commitment, employee performance.